Audit Sampah di Kawasan Pesisir Pantai Kelurahan Tanjung: Pengabdian - Sar’iyyah, Nining; Abdullah, Adi Neneng; Jariyah, Ainun; Lina, Virgilius Bate; H, Maimunah; Daud, Daud; Moset, Maria; Abdullah, Syarifah; Pano, Margaretha Sryani; Bele, Paskalia Afni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
A waste audit on the Tanjung Village coastline was conducted to identify the types, quantities, and primary sources of waste polluting the coastal area. This activity is crucial because the growth of community activities, tourism, and trade around the coast directly impacts the quality of the environment and coastal ecosystems. This Community Service activity applied direct data collection techniques by mapping locations, measuring the volume and weight of waste, and classifying it according to categories such as single-use plastic, organic, paper, glass, and metal. The audit results revealed that plastic waste dominated with the highest percentage, particularly food packaging, beverage bottles, and plastic bags originating from the activities of visitors and households in the area. This situation demonstrates the importance of better community-based waste management, environmental education, and strengthening the function of the village government in monitoring and handling waste. This audit is expected to form the basis for planning pollution mitigation programs, strengthening cleanliness policies, and plastic waste reduction campaigns to create a clean, healthy, and sustainable Tanjung Village coastline